The Diagnostic Value of β-Human Chorionic Gonadotropin, Progesterone, and Ischemia-Modified Albumin and Their Combined Use in the Prediction of First Trimester Abortions. (1st July 2014) - Osmanağaoğlu, Mehmet A.; Karahan, S. Caner; Aran, Turhan; Güven, Süleyman; Turgut, Elif; Menteşe, Ahmet; Bozkaya, Hasan
Abstract : Objective . To investigate serum levels of free β -HCG, progesterone, and ischemia-modified albumin (IMA) and their combined use in the prediction of first trimester abortions. Methods . A total of 156 pregnant women between 5 and 13 weeks of gestational age were included in this study. At admission, serum levels of free β -HCG, progesterone, and IMA were noted and all cases were divided into two groups; Group I (n = 77 ) resulted in abortion including missed abortion, incomplete/complete abortion, and inevitable abortion whereas Group II (n = 79 ) included normal pregnancies. Results . Compared to Group II, the significantly decreased value of free β -HCG progesterone and significantly increased value of IMA were found in Group I (P < 0.01, P < 0.01, P < 0.01, resp.). When combining all three parameters, sensitivity 75%, specificity 99%, PPV 98%, and NPV 76% were obtained. The multivariate logistic regression analysis revealed the free β -HCG, progesterone, and IMA independent factors in the prediction of abortions. Conclusions . The combined use of free β -HCG, progesterone, and IMA levels can be useful in the prediction of first trimester spontaneous abortions.